2018
DOI: 10.1002/bjs.10885
|View full text |Cite
|
Sign up to set email alerts
|

Omission of surgery in older women with early breast cancer has an adverse impact on breast cancer-specific survival

Abstract: Background: Primary endocrine therapy is used as an alternative to surgery in up to 40 per cent of women with early breast cancer aged over 70 years in the UK. This study investigated the impact of surgery versus primary endocrine therapy on breast cancer-specific survival (BCSS) in older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 26 publications
(35 reference statements)
2
42
1
Order By: Relevance
“…We looked to examine treatment patterns for early, invasive ER+ breast cancer in older patients, in order to investigate whether the effect of age persists in the type of treatment. Older age seemed to correlate with less surgical treatment, which is in turn associated with worse breast cancer specific survival [12][13][14]. In order to assess whether non-operative treatment in the context of age is affected by the diagnosis (DCIS vs stage I&II invasive cancer), pooled effects from the previous studies were meta-analysed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We looked to examine treatment patterns for early, invasive ER+ breast cancer in older patients, in order to investigate whether the effect of age persists in the type of treatment. Older age seemed to correlate with less surgical treatment, which is in turn associated with worse breast cancer specific survival [12][13][14]. In order to assess whether non-operative treatment in the context of age is affected by the diagnosis (DCIS vs stage I&II invasive cancer), pooled effects from the previous studies were meta-analysed.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the fact that a woman N80 y with DCIS is more probable to undergo surgery than a peer with invasive breast cancer, may be seen as a paradox, but it reflects the knowledge gaps on DCIS and the lack of acceptance for PET in this setting. Unfortunately, patient age in the setting of early breast cancer has repeatedly been shown to independently affect the decision of the physicians regarding the type of treatment that should be administered, whereas it is clear that it should not, as it has been shown that treatment de-escalation on this basis is related with worse survival [13,14,81]. All these data urge for change of attitude and clear delineation that de-escalation should not be a synonym for palliation.…”
Section: Discussionmentioning
confidence: 99%
“…43 Specifically, in women with ER-positive EIBC, surgery offers survival outcomes that are superior to primary endocrine therapy. 35 However, variation in the rate of primary surgery and survival, between older and younger women with ER-positive EIBC is widely reported. 1 2 35 44 The ability to distinguish between comorbidity and frailty is clinically relevant because these factors can be optimised, and potentially reversed (in the case of frailty), to improve rates of surgery and survival in women with EIBC.…”
Section: Discussionmentioning
confidence: 99%
“…Women who received surgery for ER-positive EIBC have better survival than women who did not. 35 Thus, the relationship between survival and surgery was explored by: (1) subgroups of women who did and did not have surgery and (2) using surgery as an explanatory variable in a Cox proportional hazards model for all women. The study specifically focused on 3-year survival because recommendations by the International Society of Geriatric Oncology and European Society of Breast Cancer Specialists for older women with breast cancer state that 'primary endocrine therapy (PET) should only be offered to elderly individuals with ER-positive tumours who have a short estimated life-expectancy (<2-3 years), who are considered unfit for surgery after optimization of medical conditions…'.…”
Section: Evaluation Of the Scarf Index's Performancementioning
confidence: 99%
“…The Bridging the Age Gap in Breast Cancer research programme sought to improve treatment decisionmaking for older women (≥70 years) with breast cancer by: 1) conducting an observational cohort study assessing breast cancer outcomes of older women, 2) developing decision support interventions (DESIs) to predict treatment outcomes and support shared decision-making, 3) testing the DESIs in a cluster randomised trial.…”
Section: Introductionmentioning
confidence: 99%